EatsEasy reimagining the food experience towards a better normal through a streamlined multi-cloud kitchen facility - Ang, Darcey Lyn C.
A new normal emerged with the onset of the COVID-19 pandemic, especially in the landscape of the global restaurant industry where food business models were altered to accommodate new dining restrictions. Among these new models, the concept of a cloud kitchen become popularized in the Online Food Delivery (OFD) service, where spaces are transformed into multiple shared kitchen facilities that only focus on food production and delivery to provide a safer, faster, and more convenient OFD experience. Despite this new option, its application in the Philippine setting is observed to be limited and in need of more efficient interventions. This study explores a systemic architectural approach for the design of a streamlined multi-cloud kitchen facility in a food district in Quezon City, specifically Tomas Morato in South Triangle, to reimagine the food experience for kitchen chefs, delivery riders, and food consumers towards a better normal. It examines the impacts of the pandemic on OFD, develops conceptual and spatial frameworks for a streamlined design solution, and applies the emerging concepts that translate to a systemic architectural design. With this project, it is argued that a streamlined multi-cloud kitchen facility can be architecturally designed to be the solution to uplift and strengthen the food service industry in the Philippines. In conclusion, this project, by exploring a systemic transformation of an urban food space into a sustainable zone for a more resilient food experience, serves as a model in the theme of 'transcendence' that jumpstarts the trend in the Philippines.